2016
DOI: 10.1017/s2078633615000338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inbreeding and individual increase in inbreeding on growth in Nilagiri and Sandyno breeds of sheep

Abstract: SummaryIndividual increase in inbreeding coefficients (ΔFi) has been recommended as an alternate measure of inbreeding. It can account for the differences in pedigree knowledge of individual animals and avoids overestimation due to increased number of known generations. The effect of inbreeding (F) and equivalent inbreeding (EF) calculated fromΔFi, on growth traits were studied in Nilagiri and Sandyno flocks of sheep. The study was based on data maintained at the Sheep Breeding Research Station, Sandynallah. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
2
1
1
Order By: Relevance
“…Regression coefficients for DWG2 and DWG3 were higher than those (−0.263 ± 0.116) reported for daily weight gain from 90 to 365 in Sandyno sheep (4) , and lower than those found for daily weight gain from 90 to 180 (−1.810 ± 0.017) and from 90 to 365 (−1.345 ± 0.083) in Baluchi sheep (2) . Finding effect for daily weight gain and no effect for body weight seems incoherent, but it is easy to explain.…”
Section: Inbreeding Effect On Phenotype and Breeding Valuescontrasting
confidence: 70%
See 1 more Smart Citation
“…Regression coefficients for DWG2 and DWG3 were higher than those (−0.263 ± 0.116) reported for daily weight gain from 90 to 365 in Sandyno sheep (4) , and lower than those found for daily weight gain from 90 to 180 (−1.810 ± 0.017) and from 90 to 365 (−1.345 ± 0.083) in Baluchi sheep (2) . Finding effect for daily weight gain and no effect for body weight seems incoherent, but it is easy to explain.…”
Section: Inbreeding Effect On Phenotype and Breeding Valuescontrasting
confidence: 70%
“…The effective population size (Ne) is a parameter widely used to indicate risk of inbreeding depression or even extinction risk. In the last 50 yr, the effective population size of several sheep breeds has drastically decreased, leading in some cases to inbreeding depression (2,3,4) . Moreover, several sheep breeds were extinct in the 20th century due to reduction of Ne.…”
mentioning
confidence: 99%
“…Significant negative effect on 6, 9 and 12 months body weight was also observed by Dorostkar et al (2012) in Iranian Moghanisheep, Gowane et al (2014) in Malpura sheep, Naghavian et al (2016) in Shirva Kordi sheep and Venkataramanan et al (2016) in Nilagiri sheep. The significant deleterious effect of increased inbreeding was observed on all fitness traits in the present study.…”
Section: Effect Of Inbreeding On Growth and Fitness Traitssupporting
confidence: 52%
“…Inbreeding depression, the decline in the value of a trait as a direct consequence of inbreeding, occurs in animal and plant populations. There was clear and irrefutable evidence for inbreeding depression in population [38,39]. The genetic studies and molecular evolutionary approaches suggested that inbreeding depression was predominantly caused by the presence of recessive deleterious mutations in populations [40].…”
Section: Discussionmentioning
confidence: 99%